Effect of glass transition on drying crack formation of maize kernels. (October 2022) - Zheng, Zhaohui; Ren, Liuyang; Wei, Shuo; Xie, Weijun; Fan, Ben; Fu, Hanyu; Yang, Deyong
Abstract : The change of temperature and moisture content during maize ( Zea mays ) kernel drying can cause glass transition, which can lead to crack formation. However, the influence mechanism of glass transition on crack formation is not clear. This work aimed to study the effect of form and process of glass transition on the crack formation. It was found that the form and process of glass transition of maize kernels were determined by the state diagram, moisture content, temperature and state distribution. Glass transition began at the corner of the kernel and extended from the surface to the centre, which was consistent with the development of cracks. The transition form, transition rate and duration of the transition state depended on drying stage and temperature, which could effectively explain the difference in the degree of cracking. This could be helpful for understanding the crack formation mechanism and optimising the operating conditions in maize drying. Highlights: Crack formation depended on the form and process of glass transition. Moisture content and temperature of corn kernel affected the glass transition process. The difference of crack degree could be explained effectively by the glass transition. Occurrence and propagation of cracks were consistent with transition of glassy state.